Phát triển chương trình bồi dưỡng năng lực dạy học stem cho giáo viên công nghệ trung học cơ sở - Bùi , Văn Hồng; Phan , Nguyễn Trúc Phương; Nguyễn , Quốc Tiệp (Tạp chí Giáo dục, 2021)
In addition to the content of technology education, the technology subject program in general and secondary schools in particular also integrates STEM education in both content and orientation of teaching methods. Therefore, in order to implement effective teaching, secondary Technology teachers must be trained to develop STEM teaching capacity. However, at present, training courses on STEM teaching competence for secondary school Technology teachers have not been developed in accordance with the characteristics of technology subjects. Through the analysis of the characteristics of STEM education, the teacher’s ability to teach STEM, and the process of developing training programs according to competence, the research results aim to develop a curriculum for fostering STEM teaching competence for Technology teachers at secondary schools, meeting the requirements of implementing the general education program issued in 2018.